Equal latency contours and auditory weighting functions for the harbour porpoise (Phocoena phocoena) - Wensveen, Paul; Huijser, Léonie A. E.; Hoek, Lean; Kastelein, Ronald A. (Journal of Experimental Biology, 2017)
This work was supported by The Netherlands Ministry of Infrastructure and the Environment [grant number 4500182046], and by matched funding from The Netherlands Ministry of Defence (administered by TNO) and the UK Natural Environment Research Council [to P.J.W.]. Loudness perception by human infants and animals can be studied under the assumption that sounds of equal loudness elicit equal reaction times (RTs). Simple RTs of a harbour porpoise to narrowband frequency-modulated signals were measured using a behavioural method and an RT sensor based on infrared light. Equal latency contours, which connect equal RTs across frequencies, for reference values of 150-200 ms (10 ms intervals) were derived from median RTs to 1 s signals with sound pressure levels (SPLs) of 59-168 dB re. 1 μPa and centre frequencies of 0.5, 1, 2, 4, 16, 31.5, 63, 80 and 125 kHz. The higher the signal level was above the hearing threshold of the harbour porpoise, the quicker the animal responded to the stimulus (median RT 98-522 ms). Equal latency contours roughly paralleled the hearing threshold at relatively low sensation levels (higher RTs). The difference in shape between the hearing threshold and the equal latency contours was more pronounced at higher levels (lower RTs); a flattening of the contours occurred for frequencies below 63 kHz. Relationships of the equal latency contour levels with the hearing threshold were used to create smoothed functions assumed to be representative of equal loudness contours. Auditory weighting functions were derived from these smoothed functions that may be used to predict perceived levels and correlated noise effects in the harbour porpoise, at least until actual equal loudness contours become available. Peer reviewed